Out-of-pocket costs, time burden, and caregiver quality of life associated with pediatric medically attended respiratory syncytial virus illnesses - Angela M. Rose; Kerra R. Mercon; Acham Gebremariam; Jamison Pike; Lisa A. Prosser (Cost Effectiveness and Resource Allocation)
Abstract Background Respiratory syncytial virus (RSV) causes a large burden of illness among infants and young children, accounting for 50,000 hospitalizations annually in U.S. children under two years of age. RSV-related illness can require outpatient, emergency department, and hospitalized medical care contributing to significant medical and nonmedical economic burden. Further, the symptoms associated with RSV can reduce quality of life in children and their caregivers. Presently, the economic burden of RSV illness for children and their caregivers is largely unresearched. The objective of this study was to estimate the financial, time, and quality of life burdens associated with pediatric RSV illness for children and their caregivers. Methods Surveys were developed to measure the out-of-pocket costs, time costs, and caregiver quality of life associated with medically attended RSV illness. Caregivers of pediatric (age 0–17 years) patients with RSV illness seen at Michigan Medicine were invited by email and text message between October 2022 and June 2023 to complete the online surveys. Results Mean out-of-pocket medical costs for outpatient and emergency department (ED) visits were more than $500 per case. Mean out-of-pocket medical costs associated with hospitalizations, with an average length of stay of 6 days, were $1290 per case. Non-medical costs ranged from $83-$267 depending on health care service utilized. Mean time spent traveling, waiting, and receiving care in outpatient and ED settings was 9 h per case. Caregivers spent an average of 3.5 days caring for their non-hospitalized child with RSV illness and 11.6 days caring for their child who was hospitalized. Quality-adjusted life years (QALYs) lost for caregivers was 0.011–0.019. QALYs lost per episode for the sick child ranged between 0.0161 and 0.087 for outpatient episodes of illness and hospitalization, respectively. Conclusions This study demonstrated the high financial burden and consequences to quality of life experienced by children with RSV illness and their caregivers, especially when the child was hospitalized due to their illness. Use of these findings will be valuable for evaluating the cost effectiveness of treatments and preventative measures from the perspective of caregivers, and understanding the complete economic burden of RSV illness.